Penanganan Kenakalan Siswa (Studi Kasus Di Mts Muhammadiyah 1 Gondangrejo Karanganyar) - FAUZI, AGUS MUHAMMAD; , Dr.Suyatmini,SE.,M.Si (2016)
The purpose of this study was to (1) Describe the factors that cause delinquency students in MTs Muhammadiyah 1 Gondangrejo Karanganyar, (2) Describe how to prevent student misbehavior in MTs Muhammadiyah 1 Gondangrejo Karanganyar, and (3) Describe the solution handling student misbehavior in MTs Muhammadiyah 1 Gondangrejo Karanganyar. This study is a qualitative research. This research was conducted in MTs Muhammadiyah 1 Gondangrejo Karanganyar. Data collection techniques used in this study is observation, interview and documentation. Data analysis techniques in this study using an interactive model of data collection, data reduction, data presentation, and conclusion. The results showed (1) The factors that cause delinquency students in MTs Muhammadiyah 1 Gondangrejo Karanganyar is a matter of family, neighborhood, and electronic media. (2) How to prevent student misbehavior in MTs Muhammadiyah 1 Gondangrejo Karanganyar preventive (prevention), and repressive (inhibits), whereas that was already by way of curative (healing) and rehabilitation (repair). (3) The solution handling student misbehavior in MTs Muhammadiyah 1 Gondangrejo Karanganyar the school plays an active role in finding solutions to handling student misbehavior among others, with the mentoring program that involves parents, for example, on how to understand the behavior of students both at school and at home, so that would be obtained methods of treatment and prevention of delinquency occurs.